A molecular simulation study of adsorption and desorption in closed end slit pores: Is there a hysteresis loop?. (6th January 2015) - Fan, Chunyan; Zeng, Yonghong; Do, D.D.; Nicholson, D.
Abstract: This paper reports detailed simulations of adsorption and desorption of argon in closed end slit pores with the aim of investigating the existence of hysteresis. The classical thermodynamic approach implies that there should be no hysteresis in a closed end pore because it assumes that the condensed phase is identical to a uniform bulk liquid and that the interface between the gas-like region and the dense adsorbate region is the same when the pore fills as when it empties. Our simulations show that hysteresis is possible and we support this assertion with evidence from a critical analysis of the classical equation. Our extensive results show that hysteresis can occur in closed end pores because of the continuous structuring of the adsorbed phase induced by the combined effects of the solid–fluid interaction and the fluid–fluid interaction. Highlights: Detailed simulation of gas in pores with one end closed. Hysteresis exists in closed end pores of nano-dimensions. Continuous structuring of the adsorbed phase is the principal reason for hysteresis. Kelvin equation with bulk liquid values is not applicable for closed end pores.